Impact of PCV7 vaccination on nasopharyngeal carriage and antimicrobial resistance among children in Turkey - Kaya Gursoy, Basak; Beyazova, Ufuk; Oguz, Melahat Melek; Demirel, Filiz; Ozkan, Secil; Sultan, Nedim; Nar Otgun, Selin (The Journal of Infection in Developing Countries, 2019)
Introduction: We aimed to evaluate the effects of 7-valent pneumococcal conjugate vaccine on nasopharyngeal carriage of Streptococcus pneumoniae and antibiotic resistance in children in a well-child clinic in a tertiary children’s hospital in Turkey. Methodology: We collected nasopharyngeal (NP) specimens from 557 two-month-old babies before vaccination. After the study population had received PCV7, NP samples were obtained from 135 babies. Antimicrobial susceptibility testing and serotyping were performed. Results: S. pneumoniae colonized in 48 (8.6%) of the 557 two-month-old babies before vaccination. The follow-up cohort consisted of 135 subjects. The prevalence of PCV7 strain decreased from 33.3% to 19.3% after vaccination. However, non-PCV7 types increased from 66.6% to 80.6% (p = 0.02). Of PCV7 serotypes, 19F was the most frequent serotype before and after vaccination. There was an increase in 6A and 15 of non-PCV7 serotypes after vaccination. Penicillin non-susceptible increased from 56.3% to 80.6% after vaccination (p =0.03). Serotypes 14, 18C, 9V and 6B, which were identified before vaccination, never colonized afterwards. Number of siblings and having sibling with older age of five were determined to be significant effective factors for SP colonization presence after vaccination and antibiotic use was negatively associated with pneumococcal carriage but associated with penicillin non-susceptibility. Conclusions: Nasopharyngeal carriage rate of S. pneumoniae dropped after PCV7 vaccination, and replacement by NVT pneumococci were also observed. Risk factors for nasopharyngeal carriage included household crowding and having a sibling age five years or older. Penicillin non-susceptibility increased in both VT and NVT strains.